2002
DOI: 10.1128/jb.184.24.7001-7012.2002
|View full text |Cite
|
Sign up to set email alerts
|

Collaborative Regulation ofEscherichia coliGlutamate-Dependent Acid Resistance by Two AraC-Like Regulators, GadX and GadW (YhiW)

Abstract: An important feature of Escherichia coli pathogenesis is an ability to withstand extremely acidic environments of pH 2 or lower. This acid resistance property contributes to the low infectious dose of pathogenic E. coli species. One very efficient E. coli acid resistance system encompasses two isoforms of glutamate decarboxylase (gadA and gadB) and a putative glutamate:␥-amino butyric acid (GABA) antiporter (gadC). The system is subject to complex controls that vary with growth media, growth phase, and growth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
173
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 127 publications
(184 citation statements)
references
References 21 publications
9
173
2
Order By: Relevance
“…hdeD, which encodes an integral membrane protein of unknown function, is located immediately downstream of hdeAB and was also induced by overexpression of both gadX and gadE (Table 3). Gel shift experiments demonstrated that both GadX (Ma et al, 2002) and GadE bind to the promoter region of these genes, suggesting that they play a direct role in their activation. Moreover, several genes encoding putative chaperones and proteases were also induced by overexpression of gadX or gadE, e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…hdeD, which encodes an integral membrane protein of unknown function, is located immediately downstream of hdeAB and was also induced by overexpression of both gadX and gadE (Table 3). Gel shift experiments demonstrated that both GadX (Ma et al, 2002) and GadE bind to the promoter region of these genes, suggesting that they play a direct role in their activation. Moreover, several genes encoding putative chaperones and proteases were also induced by overexpression of gadX or gadE, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Using genome-wide technologies such as transcriptome analysis (Velculescu et al, 1997), GadX was identified as a regulator of the glutamate decarboxylase genes from the AraC family in E. coli Ma et al, 2002). As for ToxR from Vibrio cholerae, which is an acidinduced factor and a virulence regulator, GadX has been shown to be involved in the appropriate expression of genes required for virulence of enteropathogenic E. coli (Shin et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…A 25 % reduction of gadWlacZ fusion expression was observed in the rcsB strain, leaving the possibility that RcsB might activate gadAB expression through gadW. This is however unlikely, as GadW was reported to be a negative regulator of gadAB expression (Ma et al, 2002Tucker et al, 2003). In addition, a gadW mutant was reported to resist acid as well as a wild-type strain .…”
Section: Rcsb-dependent Regulation Of Gadabc Is Not Mediated By the Rmentioning
confidence: 97%
“…3(a). The gadA, gadB, gadX and gadE fusions were described by and Ma et al (2002Ma et al ( , 2003; the limits for gadA and gadB are shown in Fig. 3(a).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation